PERAN ORANG TUA DALAM PERSIAPAN ANAK MASUK SEKOLAH TATAP MUKA DI ERA NEW NORMAL SEBAGAI ADAPTASI KEBIASAAN BARU - sutrisno sutrisno (Poltekkes Kemenkes Kalimantan Timur, 2021)
The main principle in learning in the 2020/2021 school year and academic year is the health and safety of all students, principals, teachers, education personnel, and their families. Parents have an important role in the implementation of face-to-face learning in the new normal era as a form of adaptation to new habits, starting from children's readiness before leaving for school, during travel to returning home. In addition, the role of parents in providing simple sentences related to the adaptation of new habits becomes positive affirmations which are very useful because they can provide mental support to children.